Evaluation of potential human health risks associated with Li and their relationship with Na, K, Mg, and Ca in Romania’s nationwide drinking water - Iordache, Andreea Maria; Voica, Cezara; Roba, Carmen; Nechita, Constantin (Frontiers in Public Health, 2024)
Increasing lithium (Li) demand worldwide due to its properties and role in renewable energy will raise water reservoir pollution and side effects on human health. Divergent results regarding Li concentration in water and affective disorders are found in the literature, which is why regional reports are expected. The present study evaluated the occurrence and human health risks resulting from oral exposure, respectively, and the relationship between alkali metals (Li, Na, K) and minerals (Mg, Ca) in balanced purified water (bottled) and spring water. The toxic metals (As, Hg, Pb) were measured, and the results indicate values above the detection limit of 22.3% of samples in the case of lead but not exceeding the safety limits. Depending on the water sources, such as bottled and spring water, the Li concentration varied between 0.06-1,557 and 0.09-984 µg/L. We found a strong positive correlation between Li and Na and Mg, varying between bottled and spring waters (p<0.001). Li exceeded the limit set by the Health-Based Screening Level (HBSL) in 41.37 and 19% of bottled and spring water samples. The possible side effects of Li poisoning of water resources on human health have been evaluated using the Estimated Daily Intake Index (EDI) and Total Hazard Quotient (THQ). The oral reference doses (p- RfDs) for the noncancer assessment of daily oral exposure effects for a human lifetime exceeded threshold values. The THQ index shows potential adverse health effects, requiring further investigations and remedial actions in 27.58% of approved bottled waters and 2.38% of spring waters. Based on the Li concentration found in drinking water and discussed in the present study, which is correlated with the lack of strict regulation regarding Li ingestion by humans, we can conclude that water is safe. The present study can serve decision-makers and represent a starting database with metals of interest for further clinical studies. It can also be used by decision-makers to find solutions for sustainable management of clean and safe drinking water.